Anti-cancer treatment within two weeks serves as a risk factor for clinical outcomes among cancer patients with COVID-19 - Huang, Jia-Xin; Liu, Bo; Cong, Xiao-Feng; Guan, Yan-Jie; Zhang, Yi-Qun; Song, Wei; Li, Zhi; Liu, Zi-Ling; Wang, Nan-Ya (Frontiers in Oncology, 2023)
The coronavirus disease 2019 (COVID-19) pandemic has resulted in infections among patients with cancer. Our study aimed to investigate the potential adverse impact of anti-cancer treatments within 2 weeks of COVID-19 infection on clinical outcomes in patients with cancer.: This retrospective cohort study analyzed 70 cancer patients with COVID-19 infection from the First Hospital of Jilin University in Changchun City, Jilin Province, between March and June 2022. Data on demographic characteristics, vaccination status, COVID-19 clinical classification, symptoms, complications, tumor-related characteristics, laboratory examinations and medical interventions were extracted from electronic medical record. The primary outcome of our study was Intensive Care Unit (ICU) admission. Logistic regression model was performed to investigate the association between anti-cancer treatments within 2 weeks after COVID-19 infection and the risk of ICU admission. Results: Of the 70 patients enrolled in this study, 37 received anti-cancer treatments within 2 weeks after COVID-19 infection. Patients receiving anti-cancer treatment were more likely to experience non-mild COVID-19, require oxygen therapy, develop acute respiratory distress syndrome (ARDS) and exhibit elevated inflammatory levels. The risk of ICU admission (P<0.001) and 30-day mortality after reverse transcriptase polymerase chain reaction (RT-PCR) negative conversion (P=0.007) was significantly higher in patients receiving anti-cancer treatments. In multivariate Logistic regression analysis, non-mild classification of COVID-19, anti-cancer treatments within 2 weeks and ECOG > 1were all independently associated with ICU admission after adjusting for confounder factors. The risk of ICU admission rose to 43.63 times (95% confidence interval=1.31-1452.94, P=0.035) in patients receiving anti-cancer treatments within 2 weeks. Conclusion: Anti-cancer treatments within 2 weeks of COVID-19 infection increase the risk of ICU admission and 30-day mortality after RT-PCR negative conversion in patients with cancer. It may be recommended to postpone cancer-related treatments for more than 2 weeks in cancer patients with COVID-19 infection.